2007
DOI: 10.4067/s0034-98872007000800016
|View full text |Cite
|
Sign up to set email alerts
|

Acuicultura y salud pública: La expansión de la difilobotriasis en Chile y el mundo

Abstract: (Rev Méd Chile 2007; 135: 1064-71

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 21 publications
0
6
0
4
Order By: Relevance
“…Specific MHC alleles seem to confer resistance to a number of salmonid diseases (Langefors et al 2001;Palti et al 2001;Slierendrecht et al 2001;Lohm et al 2002;Grimholt et al 2003), and disease resistance might explain better some of the MHC changes observed in our study. Salmonids in Chile are exposed to a suite of novel pathogens and diseases (Cabello 2007;Burridge et al 2010;Torres et al 2010) and some private alleles were clustered together, suggesting potential functional similarity (Fig. S2).…”
Section: Discussionmentioning
confidence: 99%
“…Specific MHC alleles seem to confer resistance to a number of salmonid diseases (Langefors et al 2001;Palti et al 2001;Slierendrecht et al 2001;Lohm et al 2002;Grimholt et al 2003), and disease resistance might explain better some of the MHC changes observed in our study. Salmonids in Chile are exposed to a suite of novel pathogens and diseases (Cabello 2007;Burridge et al 2010;Torres et al 2010) and some private alleles were clustered together, suggesting potential functional similarity (Fig. S2).…”
Section: Discussionmentioning
confidence: 99%
“…It might spread pathogens such as the ISA virus and sea lice to the native biota (Sepúlveda et al . ; Cabello ,), and escaped salmons could predate and compete with other species (Soto et al . ; Buschmann et al .…”
Section: A Brief Description Of the Structure And Socio‐economic Relementioning
confidence: 99%
“…have been found in cultured Atlantic salmon, rainbow trout, and other trouts in the United States, Scotland, Ireland, Finland, Russia, and Chile (Cabello, 2007;Lima dos Santos and Howgate, 2011). However, salmon smolts are occasionally reared in cages in freshwater lakes prior to the marine grow-out phase.…”
Section: Speciesmentioning
confidence: 99%